2024
DOI: 10.1037/sah0000434
|View full text |Cite
|
Sign up to set email alerts
|

Disability, food insecurity, and nutritional assistance in the context of COVID-19 pandemic: Interrogating the role of perceived everyday discrimination.

Abstract: The COVID-19 pandemic has amplified the need for nutritional assistance among many households, but prior research suggests that people with disabilities and other marginalized groups have been less likely to seek needed assistance due to perceived discriminatory experiences. We examined variation in the use of food assistance programs during the pandemic using data from a community survey of working-age adults with a sizeable subsample of people with disabilities in the Intermountain West region of the United … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 51 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…This exploratory study utilized multiple methods to assess the overarching research question: How does public nutritional assistance (an indicator of poverty) relate to violent crime and property crimes? In a study of individuals receiving public benefits, Ciciurkaite and Brown (2023) found that, even during the COVID pandemic, people experiencing poverty, hunger, or food insecurity continued to face many forms of discrimination. Ciciurkaite and Brown (2023) found that experiences of discrimination that were related to food benefits did diminish the positive effects of public benefits that were meant to serve individuals that were experiencing poverty.…”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
See 2 more Smart Citations
“…This exploratory study utilized multiple methods to assess the overarching research question: How does public nutritional assistance (an indicator of poverty) relate to violent crime and property crimes? In a study of individuals receiving public benefits, Ciciurkaite and Brown (2023) found that, even during the COVID pandemic, people experiencing poverty, hunger, or food insecurity continued to face many forms of discrimination. Ciciurkaite and Brown (2023) found that experiences of discrimination that were related to food benefits did diminish the positive effects of public benefits that were meant to serve individuals that were experiencing poverty.…”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
“…In a study of individuals receiving public benefits, Ciciurkaite and Brown (2023) found that, even during the COVID pandemic, people experiencing poverty, hunger, or food insecurity continued to face many forms of discrimination. Ciciurkaite and Brown (2023) found that experiences of discrimination that were related to food benefits did diminish the positive effects of public benefits that were meant to serve individuals that were experiencing poverty. Ciciurkaite and Brown's findings are not unique as similar findings had been echoed by others (Thornicroft et al, 2022;Turan et al, 2019).…”
Section: Discussion Implications and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation